Understanding predictors of caregivers’ treatment-seeking behavior for mental health: the roles of stigma, motivation, relationship, and literacy - Fitryasari, Rizki; Iswanti, Dwi Indah; Sari, Dianis Wulan; Nurlela, Lela; Marthoenis, Marthoenis; Warsini, Sri; Mulud, Zamzaliza Abdul (Jurnal Ners, 2025)
Introduction: Caregivers play a crucial role in seeking timely treatment for individuals with mental disorders. However, reliance on traditional healing practices often leads to delayed medical care. This study aims to identify predictors of caregivers' treatment-seeking efforts, focusing on the role of stigma, motivation, relationship with the patient, and mental health literacy. Methods: A cross-sectional study involving 301 caregivers of patients with mental disorders was conducted in two mental hospitals using cluster sampling. Variables studied include sociodemographic factors, caregiving burden, stigma, social support, motivation, mental health literacy, and treatment-seeking behavior. The data were collected through validated questionnaires as instruments. Multivariate regression analysis was performed to identify significant predictors of treatment-seeking behavior. Results: The study revealed that caregivers' relationship with the patient, perceived stigma, caregiving motivation, and mental health literacy significantly predicted treatment-seeking behavior (p < 0.05). Mental health literacy emerged as the strongest predictor (β = 0.349), followed by motivation (β = 0.202), stigma (β = -0.125), and relationship with the patient (β = -0.108). Together, these variables explained 23.4% of the variance in treatment-seeking efforts. Conclusions: Mental health literacy is the most influential factor in caregivers' efforts to seek medical treatment. Interventions aimed at increasing mental health literacy and reducing stigma are critical to enhancing caregivers' engagement with formal healthcare services. Findings support the development of culturally appropriate education and support programs to improve mental health outcomes.